Malignant Peripheral Nerve Sheath Tumor Related to Diffuse Neurofibroma of Chest Wall - Çakmak, Muharrem; Demırel, Ismail (My University, 2021)
Malignant peripheral nerve sheath tumors account\rfor 5–10% of all soft tissue tumors. These tumors are\rclosely related with Neurofibromatosis type 1. Alt-\rhough many such tumors have been reported in\rdifferent locations, malignant peripheral nerve sheath\rtumors arising from diffuse neurofibroma located in\rthe chest wall are extremely rare. In the present study\rwe report on a malignant peripheral nerve sheath\rtumor arising out of a diffuse neurofibroma of the\rchest wall.
Keywords: Onkoloji; Cerrahi